The impacts of media richness, blurriness, and beautification of online dating profile visual elements on dating outcomes - Dai, Minhao; Xia, Shilin (Frontiers in Communication, 2025)
IntroductionOnline dating is a popular way for individuals to connect today, and the visual elements of an online dating profile have become an essential part of online dating. The current study examined how media richness, visual blurriness, and beautification of an online dating profile’s visual elements would influence online dating outcomes.MethodsWe conducted an online dating experiment with 10 different conditions with younger adults between 18 and 35 (n = 389).ResultsThe results showed that the richer visual elements and the beautified selfie in an online dating profile predicted a number of dating outcomes, including stronger perceived positive traits, more favorable profile assessments, and stronger dating intentions. Moreover, we found such impacts to be gendered, where beautification did not change the assessment of the male profiles but significantly improved all assessments of the female profiles.DiscussionThe findings suggested some differences in how visual variations impacted online dating and revealed some interesting differences in the expectations of online dating profile visuals.